Comment on dissociation between running economy and running performance in elite Kenyan distance runners - Santos-Concejero, J.; Tucker, R. (Journal of Sports Sciences, 2016)
Mooses and colleagues suggest that running economy alone does not explain superior distance running performance in elite Kenyan runners. Whilst we agree with the multi-factorial hypothesis for Kenyan running success, we do not believe that running economy can be overlooked to the extent that it was based on this particular study. Based on the methods used and the range of athletes tested, in this response letter we question whether this study provides any basis for downplaying the influence of running economy or suggesting that other factors compensate for it to enable superior performance.